The Role of Team and Task Characteristics in R&D Team Collaborative Problem Solving and Productivity - Daley, Robert C. (Management Science, 1978)
Antecedents of collaborative problem solving in R&D teams have received little attention. Furthermore, the relationship between this form of problem solving and R&D team productivity remains unarticulated. This lacuna is addressed in the present study be analyzing the relationships between task and team, properties, collaborative problem solving and team productivity. Multiple regression was used to study the relationships among these variables. Results indicated that team cohesiveness and task certainty were robust predictors of collaborative problem solving and productivity for 45 R&D project groups. It was found that collaborative problem solving did not have a linear relationship with team productivity The collaborative problem solving-productivity relationship was further examined and it was shown that the relationship was sensitive to high and low levels for each of four predictors used in the research design (task certainty, task interdependence, team size, and team cohesiveness). These empirical findings were then translated into implications for R&D managers.